Enhancing Time Management and Prioritization Skills in Healthcare Professionals: A Simulation-Based Training Approach - Yunus, Ibad Maulana; Fadila, Fairuz Zahra Nur; Ramadani, Nataya Schartaofikea; Rohaniah, Dina; Fikri, Insan Ahmad; Humairo, Mika Vernicia (Inovasi Lokal, 2025)
Time management and prioritization are essential skills for healthcare professionals, yet many struggle with inefficiencies due to high workloads and multitasking demands. This study explores the effectiveness of a simulation-based training program designed to enhance time management and prioritization skills among healthcare workers. Using role-playing simulations, participants were exposed to realistic scenarios requiring them to manage tasks under time constraints. The training incorporated tools such as the Eisenhower Matrix and Time Blocking techniques to improve decision-making and task prioritization. Results showed a significant increase in work efficiency (from 50% to 75%), improved patient satisfaction (from 3/5 to 4.5/5), and reduced stress levels (from 8/10 to 4/10). Challenges such as communication gaps and initial resistance to new methods were identified but addressed through collaborative learning. The findings highlight the importance of structured training programs in equipping healthcare workers with practical time management skills. Recommendations include periodic training, technological integration, and organizational support to sustain improvements. These outcomes underscore the potential of simulation-based education to enhance both individual performance and organizational outcomes in healthcare settings